DMPTool - Swauger, Shea, author; The Charleston Advisor, publisher (Colorado State University. Libraries, 2015)
DMPTool is a free, open source, online tool that helps users build a comprehensive and descriptive data management plan. DMPTool is tailored to be compliant with major grant funding agencies' requirements for data management plans, provide guidance for content, and link to additional resources that users might need to complete their plans. Institutions can subscribe (for free) to integrate customized text and resources into their researcher's plans using available campus services like institutional repositories, or set up a review system for plans associated with that institution.
Advisor reviews--standard review.
Date of review: November 17, 2014.
Keywords: data management plan